Phonological Alterations Occuring In Some Children With Cerebral Palsy At YPAC Cabang Surabaya (A Case Study On Developmental Phonological Disorders In Some Children) - Evy Christya Anggari (2004)
Children show many individual differences in phonological development, and the age at which a child masters alJ sounds may vary from three to five years old. But when children have Cerebral Palsy, muscular disorder, hearing problems, neurological disorders (such as brain injury, infection, and tumor), and cognitive problems (such as in mental retardation), then their acquisition of speech is often affected. Cerebral palsy embraces the clinical picture created by injury to the brain, in which one of the components is motor disturbance. Cerebral palsy has a variety of symptoms including spasticity (tight muscles, or abnormally high muscle tone) poor balance and lack of muscle coordination. Thus, minor motors skills like writing or some speech may be affected. Concerning their language deficits and cognitive dysfunction, I am interested in making the study of phonological alterations. The speech of children with phonological disorder is marked by the three segmental alterations: deletion, insertion and metathesis of sounds for another. In collecting the data, I asked them to directly imitate me by pronouncing some Indonesian words from the list that I have made previously. After that, I recorded their speech. In analyzing the data, I transcribed their speech based on the Indonesian phonetic transcription and then classified based on their position of the words, place of articulation, and the last is based on three main types of phonological alteration: deletion, insertion, and metathesis. Afterwards, I was able to find out phonemes altered by respondents. Finally, it was discovered that respondents usually delete consonant and vowel sounds either in initial, medial, and final position of the words, while there is one respondent who never deletes any sounds in any possible positions. Most of the deleted phonemes are "difficult" phonemes, such as apiko alveolar /r/, Ill, In/, dorsovelar /kl, lg/, /x/, /J]/, and )amino alveolar Isl and /z/. Interestingly, there are two respondents who usually insert central middle /~/ before the initial position of the words. Moreover, all of the respondents often replace consonant, vowel, and diphthong sounds in any possible positions. Respondents mostly replace apiko alveolar Ir/ and /n/, dorsovelar, medio palatal /c/, /j/, /ft/, labiodental /f/ and /v/, and lamino palatal If/. Respondents usually replace those "difficult" phonemes with "easy" ones, which are produced by involving frontier parts of the vocal tracts and are usually acquired earlier than those which are produced farther in the back of the vocal tract.